Hubungan Teknik Couterpressure Massage Dengan Birth Ball Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif di PMB Wilayah Kelurahan Kembangan Selatan Kota Jakarta Barat Tahun 2023 - Zulfina, Nora; Famayanti, Arini; Hartati, Fatimah (Lembaga Publikasi Ilmiah Nusantara, 2024)
This study employed a pre-experimental method with a one-group pretest-posttest design. The sample size consisted of 30 respondents. The population included all laboring mothers in the first stage of labor with cervical dilation of 6–8 cm, selected through purposive sampling. Data collection was conducted using counterpressure with a birth ball questionnaires and the Numeric Rating Scale (NRS) for pain measurement. Data analysis was performed using the Wilcoxon test and paired t-test. The Wilcoxon test results showed a Z-value of -4.902 with an asymp.sig (2-tailed) value of 0.000 > 0.05, indicating that the data supports the conclusion that there is a significant difference before and after performing counterpressure with a birth ball. Additionally, the paired t-test revealed that the average pain level before the intervention was 8.20, while the average pain level after the intervention was 6.23. This indicates a reduction in pain intensity with a difference of 1.97, and the significance value obtained was 0.000 > 5% (p-value = 0.000 < 0.05). Therefore, the hypothesis (Ha) is accepted, meaning that counterpressure with a birth ball has a significant effect on reducing labor pain during the active phase of the first stage of labor. The study suggests that counterpressure using a birth ball can be used as an alternative non-pharmacological therapy for pain management during the active phase of the first stage of labor.